The Cummin’s Modal And Task Cognitive Complexity: Enhancing Emi Students’ Writing Skill By Implementing Frames And Self-monitoring - Nadji, Selma; Bechlaghem , Khadija (El Omda in Linguistics and Discourse Analysis, 2023)
This study examined the effect of using writing frames and post-collaboration self-monitoring strategies on improving EMI students’ writing skill at the National Higher School of Artificial Intelligence. Twenty-one first year students were part of a repeat measure experiment in a six-week intensive writing course. The writing process was investigated in terms of sequencing task complexity following a multimodal input approach which takes into consideration both cognitive and linguistic demands. Results have confirmed the current view in the literature on the role of self-regulation skills and were compatible with the claim that findings on the direct effect of task complexity on the writing input are subject to discrepancy due to distinguished task implementation factors. Recommendations for further research emphasize design and implementation variables for writing tasks, a longer time span for the treatment and incorporating methods for identifying the effect of task complexity sequencing on output complexity, accuracy and fluency as part of investigating the writing process.